Features of Electricity Distribution Using Energy Storage in Solar Photovoltaic Structure - Veremiichuk Y. (Latvian Journal of Physics and Technical Sciences, 2020)
The intensive development of renewable energy, especially solar power and wind power plants, poses risks of disrupting the balance reliability of the grid. There is the need to develop electricity storage system area, first of all, due to the global tendency to increase the demand for electricity and the number of electricity generation from renewable sources. The issue of guaranteeing electricity supply to the consumer operating in the autonomous renewable source – energy storage device – consumer system is the main criterion when selecting the installed capacity of the generator on the basis of renewable sources and energy storage device capacity. Also, the application does not allow reducing voltage fluctuations in the renewable sources – the consumer system.